Albinism, stigma, subjectivity and global-local discourses in Tanzania. Issue 3 (1st September 2016) - Brocco, Giorgio
ABSTRACT: Societal ideas and explanations of albinism at the local level in Tanzania are conceived in terms of family history, social relations, economic status, moral-religious positions, global-local flows of information and humanitarian actions on behalf of people with the congenital condition. This paper aims to show how the subjectivities of people with albinism in Tanzania are shaped and re-shaped through local moral conceptions as well as globalizing (bio)medical explanations of albinism. An exemplary case study of a 28-year-old woman, plus episodes from the lives of seven other informants with the condition, are analyzed in order to understand, on the one hand, local social relationships between people with albinism and other individuals in family and community settings, and on the other hand, the interconnections between persons with albinism and global humanitarian actors and the broadcast media. When stigma and marginalizing behaviors are perceived by individuals with albinism in Tanzania as impeding their social lives, they employ different coping strategies and discourses to enhance social acceptance.